L1 vocabulary knowledge in learning Japanese Kanji among Malay students / Uni Kazuhito - Uni , Kazuhito (2018)
This study examines the effectiveness of Malay as a learner's first language in the teaching and learning of Chinese characters ("Kanjii") in Japanese. Three vocabulary tests were administered to groups of 142, 107, and 116 native Malay-speaking Malaysian university students, respectively. Most participants had no previous knowledge of Japanese and others were beginners. The experimental group was provided with a list including written instructions in Malay and Japanese words which respectively comprised 30, 28, and 28 frequently used Kanji. The control group was given a list with the same words but without such instructions. The listed vocabulary was presented to the experimental group as pairs of two similar words. Each pair included a common component that indicated semantic similarities between Japanese and Malay. Moreover, each pair of Malay counterparts presented in the list shared a common word including meanings similar to the listed Japanese words. All participants were given 30 minutes to learn the words and another 30 minutes to answer identical multiple-choice tests comprised of 30, 28, and 28 questions, respectively. At a 5% significance level, a significant difference was found between the scores of the experimental and control groups in both tests (p < 0.001, t = 5.350; p < 0.001, t = 6.893; p < 0.001, t = 8.099). From the abovementioned results, this study concludes that explicit presentation of similarities between Japanese words and their Malay equivalents, accompanied by written instructions on the similarities in the learner's first language helps Malay-speaking students to learn Chinese characters in Japanese.